Pemaknaan Jamaah terhadap Khataman Al-Quran dalam Shalat Tarawih - Alvita Eka Rahmah (MAGHZA, 2021)
Khataman Al Quran is an act of reciting Al Quran which starts from surah al Fatihah to surah an Nas according to the mushaf Uthmani. These activities are usually carried out at certain times, for example for slametan events, praying for people who have died, or carried out in prayer to maintain memorization, especially for hafidz/hafidzah. This paper discusses one of the several momenta for the implementation of the Khataman Al Quran activity, namely the maintenance of Al Quran memorization carried out at the Tahfidzul Quran Islamic Boarding School by holding Al Quran khataman in tarawih prayers. This study aims to determine the meaning of the congregation towards this tradition by using the psychological theory of W.H. Thomas about the four basic desires of human behavior in religion. This study was designed using qualitative methods and included in field research by collecting data through interview and observation techniques. The results of this study are: first, the Khataman Al Quran in tarawih prayer has been implemented since the time of the Prophet. until now it has become part of the tradition in the Tahfidzul Quran Islamic Boarding School., second, the Tahfidzul Quran Islamic Boarding School carries out the Khataman Al Quran in tarawih prayers to follow Salafus Salafus and as a medium for murajaah., third, The results of interpreting the congregation use Thomas theory, namely the desire to be safe by maintaining their memorization, the desire to be given a response without being subject to punishment for following this tradition well, and the desire to gain new experiences by implementing the khataman Al Quran in tarawih prayers.